Power to change: Analysis of household participation in a renewable energy and energy efficiency programme in Central Australia. (December 2015) - Havas, Lisa; Ballweg, Julie; Penna, Chris; Race, Digby
Abstract: The Australian government funded a national Solar City program (2008–2013) to support communities to increase adoption of energy efficiency measures and renewable energy technology. One community was Alice Springs, a town with about 9000 households in the geographic centre of Australia. The programme offered a package of support: free energy audits, discounts for the purchase of renewable energy technology and energy efficiency measures, and ongoing information. Households that adopted solar hot water and photovoltaic systems reduced their electricity usage immediately after adoption by 10% and 34% respectively, and this was maintained in the long term. A small rebound effect of 15% was observed in the photovoltaic adopters. It was observed that, on average, households that adopted only energy efficiency measures did not have a significant reduction in their electricity usage over the long term. However, consistent with expectations, this study did show that there was a significant correlation between the number of energy efficiency measures adopted and the greatest household reduction in electricity usage. These contrary results indicate that there are additional factors involved. The connection between the effective use of measures, coincident behavioural change or increased energy awareness and greater energy reduction is discussed. Highlights: Households adopting solar hot water systems reduced total electricity usage by 10%. Households adopting photovoltaic systems reduced total electricity usage by 34%. 15% rebound effect in electricity usage by adopters of photovoltaic systems. Excluding renewable energy no significant reduction in average electricity use.